TỐI ƯU HÓA VỎ TRỤ VÀ TẤM TRÒN CÓ GÂN TĂNG CƯỜNG BẰNG NGUYÊN LÍ CỰC ĐẠI PONTRYAGIN - Minh, Trần; Hải, Nguyễn Lê (Vietnam Journal of Science and Technology, 2012)
OPTIMIZATION OF RIBBED CYLINDRICAL SHELLS AND ROUND RIBBED PLATES USING PONTRYAGIN MAXIMUM PRINCIPLE An application of the modern control theory – Pontryagin maximum principle – for solving the problem of optimizing ribbed cylindrical shells and round ribbed plates is presented in this paper. By changing the equilibrium equations in form of high-order partial differential equations into system of canonical ones, the optimum solution is to establish the Hamilton function and investigate its extreme. The calculation results show that the weight of the optimal reinfoced concrete shells and round plates can be considerably decreased.